Review on pharmacokinetics and pharmacodynamics and the aging kidney - Aymanns, Christian Kurt; Keller, Frieder; Maus, Sebastian; Hartmann, Bertram; Czock, David (Clinical journal of the American Society of Nephrology, 2010)
In people who are aged >65 years, pharmacokinetics are influenced more by the loss of kidney function than by the aging process of any other organ. A GFR of 30 to 60 ml/min, suggestive of stage 3 kidney disease, is observed in 15 to 30% of elderly people. Drug dosing must be adjusted to both changing pharmacokinetics and pharmacodynamics; the pharmacodynamics might be influenced by the aging of other organs, too. Using our NEPharm database, we extracted abstracts with pharmacokinetic parameters since 1999 from a weekly PubMed search. The recorded data were analyzed and compared with published recommendations on drug dosage and use in the elderly. Purely age-related changes in pharmacokinetic parameters were recorded from publications on 127 drugs. The analysis of our NEPharm records revealed an average (mean ± SD) age-related prolongation of half-life of 1.39-fold (corresponding to +39 ± 61%). Contrasting to common opinion, mean changes in clearance (−1 ± 54%) and volume of distribution (+24 ± 56%) were even less. The modest changes in pharmacokinetics do not suggest general dosage modifications in the elderly for most drugs. Changes in pharmacodynamics justify the common medication rule in the elderly -“start low + go slow”- especially for drugs that act on the central nervous system; however, in the case of anti-infective and anticancer therapy, the rule should be “hit hard = start high + go fast” to produce the target effect also in the elderly.
Gesehen am 28.11.2022